2021
DOI: 10.1002/cyto.b.21984
|View full text |Cite
|
Sign up to set email alerts
|

New cytometry tools for immune monitoring during cancer immunotherapy

Abstract: The success of cancer immunotherapy (CIT) in the past decade has brought renewed excitement and the need to better understand how the human immune system functions during health and disease. Advances in single cell technologies have also inspired the creation of a Human Cell Atlas to identify and describe every cell in the human body with the intention of elucidating how to “fix” the ones that fail normal function. For example, treatment of cancer patients with immune checkpoint blockade (ICB) antibodies can r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…Numerous studies have demonstrated that an elevated frequency of CD4+CD25+FoxP3+ T (Treg) cells play the role of negative immune regulation in solid tumors and hematological malignancies (Dehghani et al, 2021; Saleh & Elkord, 2020; Zheng et al, 2011). It is showed that the PD‐1/PD‐L1 axis functions as an immune checkpoint against unrestrained cytotoxic T effector cell activity‐it promotes peripheral T effector cell exhaustion and conversion of T effector cells to immunosuppressive Tregs (Park et al, 2020; Sanjabi & Lear, 2021). Increasing numbers of Tregs may accelerate T cell senescence and exhaustion and associated with high mortality and reduced survival time (Fu et al, 2007; Tang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies have demonstrated that an elevated frequency of CD4+CD25+FoxP3+ T (Treg) cells play the role of negative immune regulation in solid tumors and hematological malignancies (Dehghani et al, 2021; Saleh & Elkord, 2020; Zheng et al, 2011). It is showed that the PD‐1/PD‐L1 axis functions as an immune checkpoint against unrestrained cytotoxic T effector cell activity‐it promotes peripheral T effector cell exhaustion and conversion of T effector cells to immunosuppressive Tregs (Park et al, 2020; Sanjabi & Lear, 2021). Increasing numbers of Tregs may accelerate T cell senescence and exhaustion and associated with high mortality and reduced survival time (Fu et al, 2007; Tang et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…We enrolled aHCC patients who were also subjects of the Checkmate-040 trial from National Taiwan University Hospital (Taipei, Taiwan) and Taipei Veteran General Hospital (Taipei, Taiwan). Eligible criteria included: (1) older than 20 years old, (2) histological confirmed aHCC based on the practical guideline, (3) Child-Pugh class A, (4) Eastern Cooperative Oncology Group (ECOG) performance status 0 or 1, (5) adequate organ function for Checkmate-040 trial, (6) plan to receive nivolumab treatment, (7) no therapeutic modalities within four weeks prior to initial dose of nivolumab, and (8) did not receive any immuno-modulating medications. Patients who did not sign the informed consent form were ineligible.…”
Section: Methodsmentioning
confidence: 99%
“…Flow cytometry allows a detailed single-cell characterization of adaptive and innate immune landscapes, thereby providing a unique platform to discriminate immune cell subsets that can be exploited in an immunotherapeutic setting ( 7 ). Previously, we conducted an observational study to screen the immune cell subsets of aHCC patients and identified a significantly lower percentage of PD-1 + B cells in peripheral blood mononuclear cells (PBMCs) from aHCC patients with disease progression responses than those with disease control response after nivolumab treatment ( 8 , 9 ).…”
Section: Introductionmentioning
confidence: 99%
“…There is an increasing interest in profiling immune cell populations in tumor sites and peripheral blood and correlating this with therapy response and/or toxicities (Greenplate et al, 2016). As flow cytometry is expanding its multicolour capabilities, new studies aiming at an in-depth in site immune evaluation are needed (Sanjabi & Lear, 2021).…”
Section: Evaluation Of Immune Cell Populations In Infiltrated Versus ...mentioning
confidence: 99%